Opposing Consumption Trends for Sugar-Sweetened Beverages and Plain Drinking Water: Analyses of NHANES 2011–16 Data - Vieux, Florent; Maillot, Matthieu; Rehm, Colin D.; Barrios, Pamela; Drewnowski, Adam (Frontiers in Nutrition, 2020)
Background: Choosing water in place of sugar-sweetened beverages (SSB) can reduce added sugars while maintaining adequate hydration. The present goal was to examine 2011-16 time trends in SSB versus water consumption across US population subgroups. Methods: Dietary intake data for 22,716 persons aged >4y came from two 24-hour dietary recalls in successive cycles of the National Health and Examination Survey (NHANES 2011-16). Water intakes (in mL/d) from plain water (tap and bottled) and from beverages (SSB and not-SSB) were the principal outcome variables. Intakes were analyzed by age group, income to poverty ratio (IPR), and race/ethnicity. Time trends by demographics were also examined. Results: SSB and water intakes followed distinct social gradients. Most SSB was consumed by Non-Hispanic Black and lower-income groups. Most tap water was consumed by Non-Hispanic White and higher-income groups. During 2011-16, water from SSB declined from 322 mL/d to 262 mL/d (p<0.005), whereas plain water increased (1,011 mL/d to 1,144 mL/d) (p<0.05). Groups aged <30y reduced SSB consumption (p<0.0001) but it was groups aged >30y that increased drinking water (p<0.001). Non-Hispanic White groups reduced SSB and increased tap water consumption. Non-Hispanic Black and lower income groups reduced SSB and increased bottled water, not tap. Conclusion: The opposing time trends in SSB and water consumption were not uniform across age groups or sociodemographic strata. Only the non-Hispanic White population reduced SSB and showed a corresponding increase in tap water. Lower-income and minority groups consumed relatively little plain drinking water from the tap.